Scheimpflug Imaging in Dermatochalasis Patients Before and After Upper Eyelid Blepharoplasty. (May 2015) - Dogan, Emine; Akbas Kocaoglu, Fatma; Yalniz-Akkaya, Zuleyha; Elbeyli, Ahmet; Burcu, Ayşe; Ornek, Firdevs
Abstract Purpose: The aim of this study was to evaluate corneal parameters obtained by Scheimpflug imaging of dermatochalasis patients both preoperatively and after blepharoplasty. Materials and Methods: Sixty eyes of 30 patients (22 female, 8 male), which were operated upon for the upper eyelid, were included in the study. Patients were divided into two groups according to preoperative upper margin reflex distance (MRD): MRD < 2.5 mm (Group 1) and MRD ≥ 2.5 mm (Group 2). Preoperative and postoperative (third-month) central corneal thickness, anterior chamber depth, steepest keratometric reading, and astigmatic power vectors were the main outcomes. Results: Postoperatively, the keratometric value of the steepest meridian increased significantly in Group 1 (p = 0.018). Preoperatively and postoperatively, J0 and J45 astigmatic power vectors were similar in each group (in Group 1, for J0 p = 0.20 and for J45 p = 0.67; in Group 2, for J0 p = 0.90 and for J45 p = 0.75). The groups were similar regarding the changes in Ksteep, in astigmatic power vector J0 naJ45 (p = 0.11, p = 0.24, p = 0.55, respectively). Conclusions: The repositioning of the upper eyelid does not lead to significant changes in visual acuity, steepest keratometric reading, anterior chamber depth, central corneal thickness, or astigmatic power vector of J0 and J45. The only parameter that was significantly different from the preoperative value was the steepest keratometry reading in Group 1 patients. According to our results, blepharoplasty seems not to cause significant changes in the main corneal indices.